Auditory externalization in hearing-impaired listeners: The effect of pinna cues and number of talkers - Boyd, Alan W. (2012)
Hearing-aid wearers have reported sound source locations as being perceptually internalized (i.e., inside their head). The contribution of hearing-aid design to internalization has, however, received little attention. This experiment compared the sensitivity of hearing-impaired (HI) and normal-hearing (NH) listeners to externalization cues when listening with their own ears and simulated BTE hearing-aids in increasingly complex listening situations and reduced pinna cues. Participants rated the degree of externalization using a multiple-stimulus listening test for mixes of internalized and externalized speech stimuli presented over headphones. The results showed that HI listeners had a contracted perception of externalization correlated with high-frequency hearing loss.